On-the-job search and precautionary savings: Theory and empirics of earnings and wealth inequality - Jeremy Lise (Institute for Fiscal Studies (IFS), 2011)
I develop and estimate a model of the labor market in which precautionary savings interacts with labour market frictions to produce substantial inequality in wealth among ex ante identical workers. I show that a model of on-the-job search,in which workers are risk averse and markets are incomplete, provides a direct and intuitive link between the empirical earnings and wealth distributions. The mechanism that generates the high degree of wealth inequality in the model is the dynamic of the wage ladder resulting from the search process. There is an important asymmetry between the incremental wage increases generated by on-thejob search (climbing the ladder) and the drop in income associated with job loss (falling off the ladder). The behavior of workers in low paying jobs is primarily governed by the expectation of wage growth, while the behavior of workers near the top of the distribution is driven by the possibility of job loss.
Keywords: 330; Arbeitsmarkt; Arbeitsuche; Lohn; Risikopräferenz; Verhaltensökonomik; Vermögensbildung; Vermögensverteilung; Theorie